1997
DOI: 10.1590/s0102-311x1997000200023
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal conditions in a 7-19-year-old student population in Araraquara, São Paulo, Brazil, 1995

Abstract: The Purpose of this study was to assess the periodontal conditions and treatment needs in 7-19-year-old Brazilian school children and adolescents enrolled in the urban public schools in Araraquara, São Paulo, Brazil, in 1995, to provide baseline data for monitoring changes in their periodontal status. A sample of 1,956 school children and adolescents aged 7 to 19 years was examined by two examiners previously calibrated using the CPITN (Community Pe riodontal Index of Treatment Needs). The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…15 A relatively high percentage of children with healthy periodontium (70.43%) was observed by Varas et al in children aged 6-8 years (Santiago Metropolitan Region in Chile), while markedly lower values -22.5% -were reported by Dini et al in Brazilian 7-year-olds. 5,16 A still lower percentage was noted by Anupriya et al: in only 9.4% of the children aged 5-8 years. 14 Our own studies showed healthy periodontium to be present in 91.32% of the studied population of the 7-year-olds from a big city.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…15 A relatively high percentage of children with healthy periodontium (70.43%) was observed by Varas et al in children aged 6-8 years (Santiago Metropolitan Region in Chile), while markedly lower values -22.5% -were reported by Dini et al in Brazilian 7-year-olds. 5,16 A still lower percentage was noted by Anupriya et al: in only 9.4% of the children aged 5-8 years. 14 Our own studies showed healthy periodontium to be present in 91.32% of the studied population of the 7-year-olds from a big city.…”
Section: Discussionmentioning
confidence: 77%
“…Still higher values were quoted by Varas et al, Anupriya et al and Dini et al, who observed gingival bleeding in 27.49%, 71.9% and 76.8% of children, respectively. 5,14,16 Contrary to our study, in the research by Arnlaugsson and Magnusson, as well as Hemadneh and Ayesh, the gingival bleeding index (GBI) was used. 2,4 Among Icelandic 6-yearolds of Reykjavik examined by Arnlaugsson and Magnusson, healthy gums were noted in 26% of the children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations